Dampak Kebijakan Pemerintah dalam Pemberian Beasiswa Pendidikan (KIP) terhadap Tingkat Kelulusan Mahasiswa di Universitas Swasta Kota Jambi - Indah Sari, Pratiwi; Hakim, Lukman; Sabandi, Muhammad; Sadiah, Ati (SJEE (Scientific Journals of Economic Education), 2025)
This study aims to analyze the impact of government policy through the Smart Indonesia Card (KIP) program on student graduation rates at a private university in Jambi City. The main focus of the study is how access to educational funding through KIP affects academic achievement. The research method used is a descriptive qualitative approach, emphasizing a multi-perspective analysis of public policy. Data were collected through in-depth interviews with KIP recipient students, academic advisors, and student affairs staff. The results indicate that KIP has a significant contribution to opening access to higher education, but its effectiveness in encouraging students to complete their studies on time depends on continued policy support at the institutional level. Therefore, this study recommends that the scholarship policy be integrated with a continuous academic development program, strengthening counseling services, and regular monitoring of study progress.